2022
DOI: 10.3389/fenvs.2022.835194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Oxide Nanoparticles on the Growth of Malus hupehensis Rehd. Seedlings

Abstract: Apple replant disease (ARD) is a common disease in apple producing areas, and more and more evidence shows that soil-borne pathogens are the main factor. However, most of the drugs used to kill microorganisms are not friendly to the environment. Therefore, there is an urgent need to identify a method that can effectively eliminate these harmful microorganisms and to construct a microbial community structure that is conducive to plant growth in the soil. Herein, we use four different application technologies: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
(70 reference statements)
2
2
0
Order By: Relevance
“…In this study, the application of vermicompost favored the survival of soil bacteria (Figure 2a,b), actinomycetes (Figure 2e,f), and reduced the number of soil fungi (Figure 2c,d) in two types of soil. This is also consistent with the previous research conducted by Pan et al (2019). Pan et al (2019) showed that vermicompost significantly increased the number of bacteria and actinomyces in continuous cropping soil, and reduced the number of fungi, which effectively alleviated the obstacle of continuous cropping soil.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the application of vermicompost favored the survival of soil bacteria (Figure 2a,b), actinomycetes (Figure 2e,f), and reduced the number of soil fungi (Figure 2c,d) in two types of soil. This is also consistent with the previous research conducted by Pan et al (2019). Pan et al (2019) showed that vermicompost significantly increased the number of bacteria and actinomyces in continuous cropping soil, and reduced the number of fungi, which effectively alleviated the obstacle of continuous cropping soil.…”
Section: Discussionsupporting
confidence: 94%
“…This is also consistent with the previous research conducted by Pan et al (2019). Pan et al (2019) showed that vermicompost significantly increased the number of bacteria and actinomyces in continuous cropping soil, and reduced the number of fungi, which effectively alleviated the obstacle of continuous cropping soil. Li, Alami, et al (2022) also supported the concept of increase in the number of fungi is a symbol of a disturbed soil health system and microbial community.…”
Section: Discussionsupporting
confidence: 94%
“…Mortierella was shown to have a negative relationship with the occurrence of ARD and could play a vital role in suppressing ARD by competing for nutrients or resisting nutrients , and it exhibits strong pathogenicity .…”
Section: Discussionmentioning
confidence: 99%
“… 55 Mortierella was shown to have a negative relationship with the occurrence of ARD and could play a vital role in suppressing ARD by competing for nutrients or resisting nutrients. 56 Fusarium was severely positively interrelated with ARD in China, 57 , 58 and it exhibits strong pathogenicity. 56 Bacillus not only inhibited the reproduction of pathogenic fungi, improved microbial community structure, and enhanced plant disease resistance but also secreted catabolic phytase to increase the amount of free phosphorus in the soil, promoted phosphorus uptake by plants, and improved the crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that ZnO NPs, when properly applied, can be efficient fertilizers to increase the Zn content in plants, reduce the effect of ROS, enhance the growth of seedlings, and alleviate toxic effects generated by metals such as Cd and As [72,73]. For example, Mazhar et al [61].…”
Section: Pigment Contentsmentioning
confidence: 99%